Randomized Control Trial Comparing Moist Exposed Burn Ointment and Honey as Dressings Agents in Patients with Second -Degree Burns - Harsono, Anastasia Dessy; Wardhana, Aditya (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Many topical agents are available for the treatment of partial thickness burns. We examined Moist Exposed Burn Ointment (MEBO) and honey as dressing agents; regarding their natural antibacterial, anti-inflammatory, and wound healing properties. They have also been proven to be superior than silver sulphadiazine in treating burn wound.Methods: A total of 34 patients were randomly allocated into MEBO group and Indonesian local honey group. The dressings are changed daily, with corresponding interventions applied. The depth and extent of burn wounds were assessed upon patient’s admission and once a week for two weeks. Pain level was evaluated using the Numeric Rating Scale (NRS). The wound swabs were cultured weekly to obtain microorganisms profile. The cost-per-day of each group were counted.Result: Acute partial thickness burn in MEBO group showed faster healing compared to honey group. NRS scores for pain were also lower in MEBO group. MEBO was found to be more effective in decreasing bacterial colonization. Cost of treating wound using MEBO until complete healing was also lesser than local honey.Conclusions: As topical agent to treat partial thickness burns, MEBO is superior compared to local honey due to faster healing, better pain relief, fewer bacterial colonization and the more cost-effective usage.